GAMBARAN TINGKAT KECEMASAN PADA KELUARGA PASIEN YANG DI RAWAT DI CARDIO VASCULAR CARE UNIT (CVCU) - Fitriana " Agus; Safri " "; Jumaini " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Cardiovascular diseases is the diseases that cause by cardio and vascular function disruption that when has problems will be treated at Cardio vascular care unit (CVCU). Every physical diseases will influence psychological anyone, and the cardiovascular disease is the stressor that cause patient and family feel the anxiety. The purpose in this research is to identify overview of anxiety level on patient family that treated at cardio vascular care unit (CVCU) in the year of 2017. The research design is descriptive study. Samples of this research were 40 families that was taken by inclusion criteria by using accidental sampling technique. The instrument in this research was the anxiety level questionnaire was Hamilton Rating Scale for Anxiety (HRS-A), consist of 14 group symptom. Analysis in this research is using univariate analysis to know distribution of frequencies overview of anxiety level on patient family that treated at CVCU. The result in this research showed from 40 families the most of families was at no worried category as many as 21 families (52,5%). The conclusion is the anxiety level on patient family that treated at CVCU no worried. The result in this research recommended to hospital institution for more pay attention and know the symptom worry at every level of anxiety on patient family.  Keyword: Cardio Vascular Care Unit (CVCU), Family, Level Anxiety